Avaliação dos resultados da aplicação de um plano individual farmacêutico na melhoria do cuidado de pessoas vivendo com HIV/AIDS - Silva, Maire Rose de Sousa (2011)
The use of antiretroviral therapy resulted in the improved indicators for morbidity, mortality and quality of life of people living with HIV/AIDS. On the other hand, it contributed to HIV infection becaming a disease of chronic character evolution and potentially controllable. Before the development of this chronic profile given by the disease today, other challenges arose determining the need for new professional practices related to health care for people living with HIV/AIDS. Most studies pointed to the need to elaborate strategies aimed at comprehensive care for people living with HIV/AIDS. The objective of this study was to evaluate the results of applying an Individual Pharmaceutical Plan to improve the care of people living with HIV/AIDS. A survey was conducted from the medical records enrolled at the Medication Dispensing Unit from a Specialized Care Service on interventions and the results of viral load and CD4+ exams carried out by the application of the Individual Pharmaceutical Plan for a period of 12 months in patients on antiretroviral therapy. It was found that all 105 patients with the Individual Pharmaceutical Plan required interventions together with a multidisciplinary team for that service, totaling 1426 interventions. In the first 4 months after the implementation of the Plan (88.6%) achieved virological control and increase in the average CD4+ (557.73) cells, and in subsequent months eighth to 12º all patients maintained virological control and increase in the average CD4+ (604.16) cells, and (654.70) having a statistically significant difference before and after the application of the Plan in the three phases of evaluation. It was concluded that the interventions made from the Individual Pharmaceutical Plan allowed for the identification and solution of problems according to the individual needs of the patients and the interventions also provided a viral suppression and sustained immunologic improvement such that the results show that the implementation Individual Pharmaceutical Plan contributed to the improvement of care and quality of life of people living with HIV/AIDS, would also contribute in promoting adherence to treatment.